MONITORING PROGRAM KEPARIWISATAAN KOTA SEMARANG â€œAYO WISATA KE SEMARANGâ€ TAHUN - Setyawan, Andreas Adi; Larasati, Endang; Fathurrohman, Fathurrohman (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2013)
Ayo Wisata ke Semarang is a government program that aims to increase tourist visits to Semarang. Through this program, the government relied on three potential Semarang city tourism, religious tourism, cultural and culinary.Program which began in 2011 it contains strategic activities the government and the city of semarang tourist events . This program has a primary target increased by 1,834,886 tourists visiting in 2012. This research aims to know the implementation of the program in 2012 and how its achievement. This research was analyzed with a model monitoring Peter Rossi and using qualitative research type.This research uses descriptive qualitative research type. The research results obtained by conducting interviews to the actors involved in the programme, namely the Government of the city of Semarang, businessmen, tourists and tourist community. Researchers also spread a questionnaire to determine the level of satisfaction of tourists to tour the city of Semarang.From the results of the analysis, it can be concluded that the government reach all target the program in 2012 that have been determined. Tourists felt quite satisfied with the Semarang city tourism. The program also fosters enthusiasm some tourism businesses like T-shirt souvenirs. Promotion programs in a variety of media is a major factor in the success of this programs. Through Balanced Scorecard measurement tool, the program is achieving success of 83,69%.